PENGARUH TEKNIK JARIMATIKA TERHADAP KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA 5- 6 TAHUN DI TK ULIL ALBAB KECAMATAN WALANTAKA KOTA SERANG PROVINSI BANTEN - Ratu Yustika Rini; Isti Rusdiyani (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2018)
Paying attention to the growth, development and interests and needs of young children and by providing appropriate stimulation in early childhood can help develop early numeracy skills. The fact of the difficulty to understand the concept of counting is the factors that influence it, so it will affect the ability to count the beginning of children aged 5-6 years in the kindergarten Ulil Albab Walantaka District Serang city of Banten Province. This study aims to compare the results of pretest test of the experimental class with experimental class posttest. This research uses Quasi Experimental method or Quasi Experimental design which is used is nonequivalent control group design. The design used in this study uses posttest design only with inequivalent groups, ie experiments on 2 groups (Control class and Experiment Class). The results of this study indicate that there is a significant difference in the control class with the t-test 5,602 and the experimental class 5,861, it can be seen that t count result ≥ t table. Based on the predefined test criteria that if t count ≤ -t table or t count ≥ t table 5,602 ≥ 2.042 then H0 is rejected and H1 accepted, which means that there is difference between Posttest Class kontorl and Experiment class.